2007
DOI: 10.1016/j.atmosenv.2007.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of urban shelter-in-place—II: Residential districts

Abstract: In the event of a short-term, large-scale toxic chemical release to the atmosphere, shelterin-place (SIP) may be used as an emergency response to protect public health. We modeled hypothetical releases using realistic, empirical parameters to explore how key factors influence SIP effectiveness for single-family dwellings in a residential district. Four classes of factors were evaluated in this case-study: (a) time scales associated with release duration, SIP implementation delay, and SIP termination; (b) build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In addition, this situation of extreme conditions, especially high wind speeds, should be handled very carefully since as reported by Guyot et al [33], although the pollutant dilutes faster with increasing wind speed, the resulting dose inside the shelter could increase due to the effect of the wind over the ACH, accelerating the toxic gas transfer to the indoor. Thus, a better procedure to estimate the shelter-in-place effectiveness and the evacuation radius should include an appropriate determination of the outdoor concentration for the specific meteorological conditions, especially high wind speeds, and the ACH distribution for the affected area under these meteorological conditions as also proposed by Chan et al [2], instead of assuming a constant ACH for all the dwellings inside the affected area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this situation of extreme conditions, especially high wind speeds, should be handled very carefully since as reported by Guyot et al [33], although the pollutant dilutes faster with increasing wind speed, the resulting dose inside the shelter could increase due to the effect of the wind over the ACH, accelerating the toxic gas transfer to the indoor. Thus, a better procedure to estimate the shelter-in-place effectiveness and the evacuation radius should include an appropriate determination of the outdoor concentration for the specific meteorological conditions, especially high wind speeds, and the ACH distribution for the affected area under these meteorological conditions as also proposed by Chan et al [2], instead of assuming a constant ACH for all the dwellings inside the affected area.…”
Section: Resultsmentioning
confidence: 99%
“…Catalonia is a highly industrialized region in the north-east of Spain in which 180 companies are regulated by the Seveso II Directive [1]. In a shelter-in-place situation, air infiltration is one of the variables with the greatest influence on shelter-in-place effectiveness, as discussed by Chan et al [2] and Montoya et al [3], because it conditions the speed of toxic gas inflow and therefore the indoor gas concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior work on evaluating SIP effectiveness during large-scale chemical releases [2][3][4] assumed that the toxic load applies to time-varying concentrations in the following form:…”
Section: Toxic Load and Shelter-in-place Effectivenessmentioning
confidence: 99%
“…Recent studies have modeled the transport and dispersion of chemical compounds both outdoors and indoors under various release scenarios [1][2][3][4]. Model predictions of outdoor and indoor concentrations vary with time, but there is no consensus on how to relate time-varying air concentrations to health effects [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the first paper (Chan et al, 2007a), we conducted a parametric investigation using an idealized representation of the system. In the second paper (Chan et al, 2007b), SIP effectiveness in a residential community was assessed using realistic transport and transformation models and input parameters. In those studies, we found that SIP effectiveness depends strongly on the degree of nonlinearity in the dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%